In search of Filipina artists during the Japanese occupation (1942-1945) - Campos, Catherine Eloise Sarmiento; Yraola, Dayang Magdalena Nirvana T. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2022)
The Japanese Occupation of the Philippines represents a significant epoch in the history of our nation. Abrupt changes took place in the field of arts and culture, which prior to 1942 was enjoying the integration of Western Influences and the globalization that the American education system provided. This three-year break from the emerging modernist movement that was beginning to cement itself in the Philippine Art History saw not only the disappearance of Western Art but also of the FIlipina artists, who under the reign and propaganda of the Japanese had very limited value outside of the household. It is important to note that this dark time had not only lasting effects on the visual arts, but also on the country.

Through an investigation of library archives, museum collections, and private works, this study aims to better understand the factors that contributed to the lack of works produced during this period by FIlipina artists. Proving that although activity was limited it is in fact undeniable that these women not only existed, but despite the difficult situations they were forced into - they still created.
Thesis (Bachelor of Fine Arts in Art History)--University of the Philippines Diliman
Bibliography: leaves 68-72
Keywords: Women artists -- Philippines; World War, 1939-1945 -- Women -- Philippines; World War, 1939-1945 -- Artists -- Philippines; Philippines -- History -- Japanese occupation, 1942-1945.